Pengaruh Pengetahuan Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak di Kota Tondano - Kewo, Cecilia Lelly; Manaroinsong, Johny; Lumowa, Angelina Adeleida (Journal of Innovation in Management, Accounting and Business, 2024)
Compliance with paying taxes is a taxpayer who is obedient and fulfills and carries out tax obligations in accordance with the provisions of tax legislation Many factors influence taxpayer compliance, including tax knowledge and tax sanctions. This research aims to examine the influence of tax knowledge and tax sanctions on the level of taxpayer compliance in paying land and building tax (PBB). The object of this research is South Tondano District. The method in this research uses quantitative methods with the data analysis technique used, namely multiple linear regression analysis. The data collection technique was obtained by administering a questionnaire. The results of the research found that in the partial T test the significance value of the variable tax knowledge and tax sanctions had a positive and significant effect on the taxpayer compliance variable.